Those angry days : Roosevelt, Lindbergh, and America's fight over World War II, 1939-1941 - Olson, Lynne (Random House, 2013)
Traces the crisis period leading up to America's entry into World War II, describing the nation's polarized interventionist and isolationist factions as represented by the government, in the press, and on the streets.